Automation & Muslim Scientists - Haque, Anwar Ul (International Journal of Pathology, 2018)
Automation fascinates everyone! It’s now almostubiquitous; sparing no area of life; watches &clocks, toys, kitchen & household gadgets, communicationequipments, transport services andhospitals and laboratory equipments all haveplenty of automation! With power of electricityand computers automation has seen logarithmicgrowth explosion! But when did real and substantialautomation begin? Many will say that itperhaps began in the last century or at the most acentury prior; without electricity no question ofautomation; nothing could be farthest from truth!Greek scientists had done some initial work